Simulated annealing technique for reducing communication in mesh networks - Salleh, Shaharuddin (Faculty of Science, 2005)
This report is the compilation of our research work under Vot no. 75083 (Fundamental) at the Department of Mathematics, Universiti Teknologi Malaysia. The work consists of four main problems of study. First, we look at the single-row transformation of complete graphs into single rows. This problem involves the application of single-row routing into pair-matching problems such as channel assignments in the cellular telephone network systems. The problem is generalized and extended by involving the cliques of connected graphs for mapping and transforming these nodes into single-row nodes. We then discuss the wireless ad hoc network application on a mesh network for single-casting, multicasting and broadcasting using a model called FRECAST. Finally, the problem extends to a computational model called SPLAI using finite-element method for the wireless sensor networks. This segment of the work is capable of locating the sensor nodes in a network using a dynamic coordinate system based on the coronas and wedges. The output from the research project consists of one book, six journal papers and two proceedings papers (all at the international level), and four softwares.